2022
DOI: 10.1111/ppl.13800
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilisation with a consortium of growth‐promoting bacterial strains improves the nutritional status of wheat grain under control, drought, and salinity stress conditions

Abstract: We investigated the effect of plant growth‐promoting bacterial strains (PGPB) as biofertilisers on the grain metabolic composition of durum wheat (Triticum durum Desf.). To this aim, we conducted a greenhouse experiment where we grew durum wheat plants supplied with a biofertiliser consortium of four PGPB and/or chemical fertiliser (containing nitrogen, phosphorus, potassium, and zinc), under non‐stress, drought (at 40% field capacity), or salinity (150 mM NaCl) conditions. Nutrient accumulations in the grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 67 publications
6
15
0
Order By: Relevance
“…Higher levels of hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) in the present research revealed oxidative stress induced by chromium, in which these oxidative markers demonstrated a clear decreasing trend in response to fertilization/supplementation treatments under stress, especially in PGPB-treated plants (Figure A). This result is in agreement with previous studies that documented an increment in the levels of H 2 O 2 and MDA in various plant tissues under heavy metal-induced stress and resulted in intense oxidative damage. , In addition, a decrement in H 2 O 2 and MDA accumulation in plants treated with PGPB and OSW under heavy metal stress was previously reported. , One explanation for the higher detoxification of H 2 O 2 and MDA in fertilized plants under chromium-induced stress can be the higher stimulation of antioxidant enzymes and metabolites involved in the ASC/GSH pathway (ASC, GSH, APX, DHAR, MDHAR, GR, and GPX) in response to OSW-containing treatments (Figure A,B) and direct ROS-detoxifying enzymes (POX, SOD, and CAT) in PGPB-treated plants (Figure B). The association between detoxifying excess ROS in plant cells and improving the antioxidant protection mechanisms was previously reported .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher levels of hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) in the present research revealed oxidative stress induced by chromium, in which these oxidative markers demonstrated a clear decreasing trend in response to fertilization/supplementation treatments under stress, especially in PGPB-treated plants (Figure A). This result is in agreement with previous studies that documented an increment in the levels of H 2 O 2 and MDA in various plant tissues under heavy metal-induced stress and resulted in intense oxidative damage. , In addition, a decrement in H 2 O 2 and MDA accumulation in plants treated with PGPB and OSW under heavy metal stress was previously reported. , One explanation for the higher detoxification of H 2 O 2 and MDA in fertilized plants under chromium-induced stress can be the higher stimulation of antioxidant enzymes and metabolites involved in the ASC/GSH pathway (ASC, GSH, APX, DHAR, MDHAR, GR, and GPX) in response to OSW-containing treatments (Figure A,B) and direct ROS-detoxifying enzymes (POX, SOD, and CAT) in PGPB-treated plants (Figure B). The association between detoxifying excess ROS in plant cells and improving the antioxidant protection mechanisms was previously reported .…”
Section: Discussionsupporting
confidence: 93%
“…These Gram-positive bacteria are free-living microorganisms in soil, which can affect the agronomic and physiological traits of crops , and can also act as a primary antibiotic by producing specific metabolites . Such abilities in plant growth-promoting functions are considered one of the best strategies to manage soil fertility and crop nutritional status by replacing synthetic chemical fertilizers. , …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is widely recognized that a crop’s amino acid composition correlates with its increased nutritional and health-promoting quality. , The free amino acids in B. oleracea are precursors of metabolites like glucosinolates, which have strong effects on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Biofertilizers, such as plant-growth-promoting bacteria (PGPB), are promising alternatives to avoid soil and environmental degradation introduced because of over usage of chemical supply of macronutrients such as nitrogen, phosphate, and potassium, necessary for plant growth, in particular under intensive cropping . PGPB inoculation of seeds can stimulate the growth of plants by improving nutrient availability, protecting plants from diseases, triggering plant hormones, decreasing of ethylene levels in plants, and making plants more resistant to environmental stressors. , Besides their role in rhizosphere soil fertility through organic matter recycling, some PGPBs can create symbiotic interactions with their host plants . PGPBs have a range of strategies to promote plant growth and health, including symbiotic fixation of atmospheric nitrogen; the release of siderophores and phytohormones including gibberellins, auxins, and cytokinin; solubilizing phosphorus (P) and other minerals; and synthesis of enzymes that relieve stress. , …”
Section: Introductionmentioning
confidence: 99%
“…These plant growth-promoting bacteria (PGPB) help host plants grow in both optimum and stressful conditions through various intricate mechanisms and subtle signaling cues that are not yet fully understood [ 5 , 6 ]. However, PGPB could manipulate phytohormonal signaling, enhance the solubilization of minerals, and trigger numerous other mechanisms to improve plant stress tolerance coordinately [ 7 , 8 ]. Therefore, some plants inoculated with PGPB strains were less negatively affected by abiotic stress because the PGPB could (at least partially) restore yield [ 9 ] by enhancing plant-water relations, ion homeostasis, and photosynthetic efficiency under saline conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%